Characterization of Natural Reinforcements and their Composites - Karahan, Mehmet; Karahan, Nevin; Ozkan, Fatma; Yildirim, Kenan (Journal of Composites and Biodegradable Polymers, 2021)
In this study, the mechanical properties of flax, jute and jute/carbon woven fabrics, and their composites were investigated and compared with 3K carbon fabric composites. Mechanical properties of yarn, fabric and composites were separately investigated and compared for each scales. In addition, yarn and fabric structures were characterized. It was found that, fabric structure, yarn physical properties and fiber cross-section and fiber molecular structure parameters of reinforcement have seriously effect on the composite mechanical properties. It can be concluded that fabric tensile strength attribute to composite tensile strength, but there was not a direct relation between fabric tensile strength and composite tensile strength. The tensile strength of natural fiber fabrics were determined to be significantly reduced depending on the temperature increasing. This condition should be considered as a important limitation for composite applications of natural fibers. Mechanical test results are proved that natural fiber composites not to be an important alternative to conventional composites.